MEMAKNAI FILM DIRTY VOTE SEBAGAI PARRHESIA MICHEL FOUCAULT - Oktavianus Baylon, Ovan; Agung, Epifanius; Syukur, Daniel Oktaviano; Panjo, Saverinus; Gombol, Kristian Panusi (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to reinterpret the Dirty Vote film as Michel Foucault's act of parrhesia (telling the truth). This study uses a qualitative descriptive method with a literature study approach. The author collects various literature such as books, journals, and articles in books that are relevant to the research topic. The various literatures are then processed, analyzed, reviewed, and interpreted to be further elaborated in this study. The results of this study show that the Dirty Vote film is actually a film that tells the truth regarding the fraud in the 2024 Election. Therefore, this film can be interpreted as Foucault's parrhesia. This claim is based on the fact that the substance of this film actually reflects four elements of parrhesia, namely, parrhesia is associated with freedom of speech, parrhesia is always associated with truth, parrhesia in relation to danger and parrhesia is associated with duties and obligations. As parrhesia, this film is an attempt to re-establish the truth that has been monopolized by the regime. More than that, this film is seen as a critical voice that is useful for the growth of democracy in Indonesia, at least criticizing the authorities so that they do not act arbitrarily.